IDENTIFIKASI PROFIL ASAM AMINO DAN LEMAK BLACK SOLDIER FLY LARVAE MENGGUNAKAN PAKAN BUNGKIL DAN SISA MAKANAN - Zuliyan Agus Nur Muchlis Majid; Linda Rahmawati; Novianti Adi Rohmanna (Jurnal Teknologi Industri Pertanian, 2023)
As the world's largest palm oil producer, Indonesia has enormous potential for producing palm kernel expeller waste. Only 7% of Indonesia's palm kernel expeller (PKE) is processed into animal feed. It is necessary to utilize both wastes from palm oil processing and the workers' environment to support certification in palm oil plantations. This research aims to identify amino acid and lipid profile, total protein, fat, feeding rate, and survival rate BSFL using a palm kernel expeller for feed. The feed experiment in this research was PKE, fermented PKE, PKE with food waste, and fermented PKE with food waste as a control. The optimum result was fermented PKE with food waste with a protein total of 51.45%. Using BSFL for feed should have high protein content and low fat. The fat of BSFL fermented PKE with food waste is lower than BSFL with food waste. The feeding rate, survival rate, and BSFL mass are lower than BSFL with food waste. BSFL has the potential to reduce PKE waste and domestic food waste. The amino acid profile of BSFL PKE with household food waste consists of L-Glutamic Acid, L-Leucine, L-Arginine, L-Tyrosine, L-Valine, and L-Phenylalanine. L-Glutamic acid was the highest amino Acid in BSFL (36.396 g/kg). The type of amino Acid in BSFL is suitable for animal feed. The lipids in BSFL PKE with household food waste are lauric acid, oleic acid, unsaturated fat, monounsaturated fat, palmitic acid, myristic acid, and linoleic acid. The highest content of lipids is lauric acid (12.126%). The type of fat in BSFL can be used to produce biodiesel. Keywords: black soldier fly larvae, palm kernel expeller, amino acid profile, fat profile, household food waste